The use of an inactivated vaccine in farmed Nile Crocodiles (Crocodylus Niloticus) for the control of Mycoplasma Crocodyli infection - Van Vuuren, Moritz (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.